ANALISIS KINERJA KEUANGAN BCA PERIODE 2011-2015 - Dian Indah Sari (Universitas Bina Sarana Informatika, 2017)
Abstract - Financial statement analysis will help the company to estimate the level of risk, uncertainty and result in the formulation of a better plan. Financial statement analysis aims to determine the extent to which the achievement of work has been achieved by all divisions in the company. One of the financial statement analysis is Profitability ratio. Profitability ratios are used to measure the company's ability to earn profits. The purpose of this study is to determine and identify financial performance at Bank Central Asia Tbk period 2011 to 2015. In this study, the authors use three types of data collection methods is library research Reading literature and books that examine theories about profitability ratios and the theoretical basis of the content of writing. Observations of non-behavioral methods of observation of financial statements published by BCA Tbk during the period of 2011 and 2015. The method of taking the conclusion that after the analysis process has been completed, then the conclusion is drawn by drawing conclusions from the data analysis done before. Based on the results of the discussion can be summarized as follows based on the financial statements of BCA there is a decrease in OM from 2011 to 2015. Based on the financial statements of BCA there is a decreased NPM from 2011 to 2015. Based on BCA's financial statementsthere is an increase of ROI value from 2011 to 2015. Based on financial statements BCA there is a decreased the value of ROE from 2011 to 2015. Based on BCA's financial report, there is an increase of ROA value from 2011 to 2015.Key words :Ratio Analysis, Financial Performance, Profitabiliy